Integrated Transcriptomic and Metabolomic Characterization of the Low-Carbon Response Using an ndhR Mutant of Synechocystis sp. PCC 6803. Issue 3 (17th January 2015) - Klähn, Stephan; Orf, Isabel; Schwarz, Doreen; Matthiessen, Jasper K.F.; Kopka, Joachim; Hess, Wolfgang R.; Hagemann, Martin
Abstract : Acclimation to changing CO2 levels by Synechocystis sp. PCC 6803 includes coordinated changes in gene expression and metabolism, whereby small RNAs and the transcriptional regulator protein NdhR perform distinct regulatory functions. Abstract: The acquisition and assimilation of inorganic carbon (Ci ) represents the largest flux of inorganic matter in photosynthetic organisms; hence, this process is tightly regulated. We examined the Ci -dependent transcriptional and metabolic regulation in wild-type Synechocystis sp. PCC 6803 compared with a mutant defective in the main transcriptional repressor for Ci acquisition genes, the NAD(P)H dehydrogenase transcriptional regulator NdhR. The analysis revealed that many protein-coding transcripts that are normally repressed in the presence of high CO2 (HC ) concentrations were strongly expressed in ∆ ndhR, whereas other messenger RNAs were strongly down-regulated in mutant cells, suggesting a potential activating role for NdhR. A conserved NdhR-binding motif was identified in the promoters of derepressed genes. Interestingly, the expression of some NdhR-regulated genes remained further inducible under low-CO2 conditions, indicating the involvement of additional NdhR-independent Ci -regulatory mechanisms. Intriguingly, we also observed that the abundance of 52 antisense RNAs and 34 potential noncoding RNAs was affected by Ci supply, although most of these molecules were not regulated through NdhR. Thus, antisense and noncoding RNAs could contribute to NdhR-independent carbon regulation. In contrast to the transcriptome, the metabolome in ∆ ndhR cells was similar to that of wild-type cells under HC conditions. This observation and the delayed metabolic responses to the low-CO2 shift in ∆ ndhR, specifically the lack of transient increases in the photorespiratory pathway intermediates 2-phosphoglycolate, glycolate, and glycine, suggest that the deregulation of gene expression in the Ɗ ndhR mutant successfully preacclimates cyanobacterial cells to lowered Ci supply under HC conditions.